Working Under Pressure—Mental Health and Life Satisfaction Among Elite Coaches in Norway - Tom Henning Oevreboe; Andreas Ivarsson; Göran Kenttä; Ann Kristin Skrindo Knudsen; Anne Reneflot; Anne Marte Pensgaard (International Sport Coaching Journal, 2026)
Working as a coach within a high-performance context is a demanding profession that may adversely affect mental health. However, empirical knowledge concerning the mental health of elite coaches remains limited. Consequently, this study investigated mental distress among elite coaches in Norway, its associations with work environment factors and life satisfaction, and the prevalence of diagnosable mental disorders. A two-phase design was adopted. In Phase 1, 114 coaches completed an online self-report questionnaire assessing mental distress, work environment, and life satisfaction. Coaches identified as “at-risk” for a mental disorder were subsequently invited to Phase 2, which consisted of structured diagnostic interviews using the Composite International Diagnostic Interview. In Phase 1, 35.1% of coaches reported “at-risk” scores for mental health problems, with symptoms of insomnia, depression, and anxiety most frequently observed. In Phase 2, 28 coaches participated, of whom 46.4% met diagnostic criteria for a mental disorder. Work-related variables particularly psychological safety, unpredictability, role expectations, and work–life imbalance were more strongly associated with both mental health challenges and life satisfaction than others. These findings highlight the importance of promoting sustainable work environments and ensuring access to early intervention, treatment, and adequate resources to support mental health challenges in elite coaching.